Safety of UGS Operation in terms of the Importance of Primary Factors of Tightness of Structures - HORÁKOVÁ, Markéta; BUJOK, Petr; KLEMPA, Martin; KUNZ, Antonín; KŘÍSTEK, Matěj; VAŠEK, Milan (GeoScience Engineering, 2020)
Underground gas storage (UGS) has become an essential part of gas transmission systems in all developed industrial countries. This is because transit pipelines transporting natural gas to consumers are limited by the maximum flow capacity and are not able to cover the increased seasonal or peak demand. UGS facilities then guarantee the security and reliability of gas supplies, especially in the event of a transit transmission failure. The actual safety of UGS operation is then given by the reliability of storage structures, technical and technological equipment, i.e. the so-called primary and secondary tightness. The article evaluates the primary conditions of tightness on selected UGS operated by MND Gas Storage a. s. Hodonín and MND Gas Storage Germany GmbH, Germany. These are the Uhřice, Uhřice-South (Czech Republic) and Hähnlein and Stockstadt (Germany) reservoirs. Keywords: Geology; Tectonics; Tightness; Underground gas storage. DOI 10.35180/gse-2020-0038